2023
DOI: 10.3390/su15042855
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood Strategies and Their Determinants among Informal Households in Calabar, Nigeria

Abstract: The purpose of investigating livelihood strategies is to seek patterns that can be acted upon in order to improve livelihood prospects. This paper assesses household livelihood strategies and their determinates by asking (1) how urban households manage and mobilise resources and (2) how they combine assets—emphasising the existing strategies they adopt and their outcomes. Using a mixed-method cross-sectional design, four informal settlements were surveyed. Household questionnaires were developed and used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Large household sizes would convey a considerable responsibility to the household heads in a bid to cater for the household. The study aligns with [30], who reported that people appear to be more committed to whatever they do when they have a large household size that depends on them for food, shelter, and clothing.…”
Section: • Socioeconomic Characteristics Of Agricultural Extension Pe...supporting
confidence: 87%
“…Large household sizes would convey a considerable responsibility to the household heads in a bid to cater for the household. The study aligns with [30], who reported that people appear to be more committed to whatever they do when they have a large household size that depends on them for food, shelter, and clothing.…”
Section: • Socioeconomic Characteristics Of Agricultural Extension Pe...supporting
confidence: 87%
“…Water stress, inequitable access to water supply, inequalities and inadequate financing for established water sources, and lack of information about the state of water resources and their use still exist in the city. The increasing frequency and intensity of water shortage in the region has significantly impacted health and livelihood opportunities, with many informal residents lacking access to water supply [40].…”
Section: The Study Areamentioning
confidence: 99%
“…Such literature interprets household vulnerability in terms of objective household characteristics, for example, education, employment status, number of dependents, age, and property. ( [23,[43][44][45][46][47][48]. Based on the above literature, we used the vulnerability of middle-income households as the dependent variable to analyse the determinants of middle-income household vulnerability at three levels: demographic, household, and regional.…”
Section: Model Settingmentioning
confidence: 99%